Heather Höpfl's storytelling. Issue 2 (15th March 2017) - Flory, Marja; Durant, Rita; Magala, Slawek; Boje, David; Downs, Alexis
ABSTRACT: This paper brings to light stories of Heather Höpfl. Its purpose is to show how Heather was and is present for us. We also illustrate Professor Dr Heather Höpfl's contribution to organization theory, specifically her discourse of the maternal organization.